Study on synergistic toughening of polypropylene with high-density polyethylene and elastomer-olefin block copolymers under ultrasonic application. (16th June 2018) - He, Xuelian; Shi, Jiaji; Wu, Lei; Jiang, Pingkai; Liu, Boping
Abstract: In this study, we prepared the blends of polypropylene (PP) and high-density polyethylene (HDPE) with elastomer-olefin block copolymers (OBC) using an ultrasonic twin-screw extruder and investigated the mechanical, thermodynamic, and rheological properties of the blends. We examined the interfacial interactions among PP, OBC, and HDPE and observed that the PP/OBC/HDPE blends formed a core-shell structure with HDPE as the core and OBC as the shell. The crystallization temperature as well as the crystallinity of the blends were improved thanks to the heterogeneous nucleation between PP- and OBC-covered HDPE particles. Moreover, the impact strength of PP/OBC/HDPE blends was increased by three times as compared with PP because of the addition of 10 phr OBC and 15 phr HDPE; however, the viscosity increased slightly. Furthermore, it was evident from the fracture surface morphologies of PP/OBC/HDPE blends that the OBC-covered HDPE particles became smaller under the application of ultrasonic irradiation; hence, the interfacial interactions between the particles and the PP matrix were enhanced and the impact strength of the blends was improved.